"Consent Is F#@king Required": Hashtag Feminism Surrounding Sexual Consent in a Culture of Postfeminist Contradictions. (December 2021) - Kettrey, Heather Hensman; Davis, Alyssa J.; Liberman, Jessica
Hashtag feminism exists in a time of postfeminist contradictions marked by the simultaneous existence of popular feminism and popular misogyny. In one such contradiction, popular feminism has led women to expect the successful negotiation of sexual consent, while popular misogyny permits the circulation of traditional sexual scripts that disregard the necessity of consent. In this study, we analyze messages conveyed through digitized narratives of sexual consent posted on Tumblr, a social media site that is popular among feminist activists, to identify the ways that users construct meaning around the dissonance between expectations for consent and the inequalities that inhibit its negotiation. We specifically explore whether hashtag feminism navigates postfeminist contradictions in a way that simultaneously calls out misogyny and calls on feminism. We find that the Tumblr posts in our sample did both, albeit in a manner that failed to offer tangible solutions to the problem at hand. Calls on feminism were largely limited to tagging feminist allies and recirculating existing feminist campaigns. Thus, we argue that the hashtag ultimately became a handoff to a larger feminist abstraction. Future research should explore conditions under which activists link tangible issues, actors, and agendas to an otherwise abstract popular feminism.